Erik Ringmar: Identity, Interest and Action: A culturel explanation of Sweden's intervention in the Thirty Years War. (Cambridge University Press, 1996). 284 s., 40 £. - Ladewig Petersen, E. (Historie/Jyske Samlinger, 1998)
-